Correlação diagnóstica entre a citologia aspirativa por agulha fina e a histopatologia de tumores cutâneos e subcutâneos em cães - Mello, Camila Benaduce Emanuelli (2020)
The skin and its cutaneous adnexa are susceptible to a variety of tumoral neoplastic and non-neoplastic injuries and the histopathology is the gold standard technique to classify the lesion. However, the histopathology requires sedation or general anesthesia of the patient to sample collection, it is necessary to perform fixation of the tissues, and, consequently, release the diagnosis is slower. On the other hand, the cytology comprises the study of the cells to try evaluating if the specimen is benign or malignant. The cytology sample collection is simple, fast, low coast, and, in most cases, painless and it is not necessary to sedate the animal. Besides that, releasing cytological results is faster than histological results. Among the different cytological techniques to acquire samples there is the fine needle aspiration cytology (FNAC) which is widely used and studied in veterinary medicine as an important screening and assistant diagnosis tool. The aim of this retrospective and prospective study was to establish the diagnostic agreement between FNAC and histopathology performed in cutaneous and subcutaneous tumors in dogs, to determine the accuracy as well as the sensitivity, specificity, positive predictive value (PPV) and negative predictive value (PPN) of FNAC in diagnosing cutaneous and subcutaneous neoplasms in dogs. Cytological samples from integumentary lesions in dogs collected by FNAC, between January 2017 and May 2019, archived in the Laboratory of Veterinary Clinical Analysis (LACVET) at Federal University of Santa Maria (UFSM), and for those there was the respective histopathological exam, performed at Veterinary Pathology Laboratory (LPV-UFSM), were included in the experimental design and reviewed. Cytological samples ealuation was performed by a clinical pathologist with three years of experience and who did not know the histopathological result. Samples were classified as non-neoplastic (cyst lesion and inflammation) and neoplastic, according to origin cellular in epithelial, mesenchymal, round cell tumor and melanocytic tumor. Indeed, always as possible, the neoplasms were classified in the specific categories and in benign or malignant. Eighty-five cytological samples were revaluated. Of these, 70 were classified as neoplastic and 68 had the diagnosis of neoplasm confirmed by histopathology. Fifteen cytological slides were classified as non-neoplastic and, among them, 11 had the diagnosis confirmed by histopatological evaluation. In two cytological samples, it was performed false-positive diagnoses and in four a false-negative diagnoses. Overall, the cytology accuracy in diagnosing cutaneous and subcutaneous tumors was 93% (79/85). In diagnosing neoplasms, the FNAC had a sensitivity of 94,44% (68/72), a specificity of 84.62% (11/13), PPV of 97,14% (68/70) and PPN of 73.33% (11/15). In conclusion, the FNAC is an excellent diagnostic auxiliary tool for cutaneous and subcutaneous tumors in dogs. The technique displays possible disadvantages as obtaining cytologic samples non-diagnostic or false-negative and false-positive results. Nevertheless, the FNAC presents very high sensitivity in diagnosing neoplastic lesions. Therefore, aspiration cytology must be performed always as available in the clinic veterinary routine, being a strong support to prompt conduction in the clinical approach of the patient.